2022
DOI: 10.1021/acsomega.2c04517
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of Metal–Organic Frameworks for Ammonia Capture from H2/N2/NH3 Mixtures

Abstract: The separation of ammonia from H2/N2/NH3 mixtures is an important step in ammonia decomposition for hydrogen production and ammonia synthesis from H2 and N2 based nonaqueous technologies. Metal–organic frameworks (MOFs) are considered as potential materials for capturing ammonia. In the present work, high-throughput screening of 2932 Computation-Ready Experimental MOFs (CoRE MOFs) was carried out for ammonia capture from H2/N2/NH3 mixtures by Grand Canonical Monte Carlo (GCMC) simulations. It was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Although several MOFs have been explored, the number of MOFs reported for NH 3 capture from complex environments remains limited. Liu et al [ 142 ] conducted a high-throughput computational screening (HTCS) of 2932 CoRe MOFs based on grand canonical Monte Carlo (GCMC) simulations to screen for the optimal MOF for NH 3 capture from humid gas. They found that the key to a high NH 3 capture performance was affinity or Henry’s constant of MOFs toward NH 3 and water molecules.…”
Section: Porous Solids For Nh 3 Adsorptionmentioning
confidence: 99%
“…Although several MOFs have been explored, the number of MOFs reported for NH 3 capture from complex environments remains limited. Liu et al [ 142 ] conducted a high-throughput computational screening (HTCS) of 2932 CoRe MOFs based on grand canonical Monte Carlo (GCMC) simulations to screen for the optimal MOF for NH 3 capture from humid gas. They found that the key to a high NH 3 capture performance was affinity or Henry’s constant of MOFs toward NH 3 and water molecules.…”
Section: Porous Solids For Nh 3 Adsorptionmentioning
confidence: 99%
“…[2,3] This process per year produces about 130 million tons of ammonia with about 1.8 % of total CO 2 emissions, but consumes about 1 % of the global energy supply. [4][5][6][7] Therefore, much efforts have been put into developing alternative strategy for the Haber-Bosch process, such as photocatalytic, [8,9] biological, [10,11] and electrocatalytic methods. [12,13] Among them, electrocatalysis is considered as a promising method for sustainable production of NH 3 at moderate conditions, driven by renewable hydrogen, solar, wind, and nuclear energy.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial production of ammonia is heavily relied on the traditional Haber‐Bosch process, which requires high‐temperature and high‐pressure reaction conditions to dissociate the N≡N bond (946 kJ mol −1 for the bond energy) [2,3] . This process per year produces about 130 million tons of ammonia with about 1.8 % of total CO 2 emissions, but consumes about 1 % of the global energy supply [4–7] . Therefore, much efforts have been put into developing alternative strategy for the Haber‐Bosch process, such as photocatalytic, [8,9] biological, [10,11] and electrocatalytic methods [12,13] .…”
Section: Introductionmentioning
confidence: 99%